In Silico Study of Novel Ketorolac as selective Cyclooxygenase-2 (COX-2) - Dewi, Tanaya Jati Dharma (Proceeding Annual Symposium on Hajj and Umrah Medicine; Vol 1 (2022): Proceeding Annual Symposium on Hajj and Umrah Medicine, 2022)
Ketorolac is a non-selective non-steroidal anti-inflammatory drug (NSAID). Ketorolac works by inhibiting the enzymes Cyclooxygenase-1 (COX-1) and Cyclooxygenase-2(COX-2). Because it also interacts with it, it gives several side effects, especially on digestion. This study aimed to design and obtain a novel ketorolac, a modification of the ketorolac compound that is selective and does not interact with it. Modify the structure by adding a substituent at the para position in the benzene ring. The method was carried out in silico with molecular docking. Predictions were made from the physicochemical properties, ADME as a pharmacokinetic profile, and its toxicity using pkCSM and Protox online. The results showed that compound J had a better affinity than ketorolac for the Cyclooxygenase-2(COX-2) receptor and had no affinity for the Cyclooxygenase-1 (COX-1) receptor because it showed a positive docking score. Still, on the other hand, it showed different results. lack of adherence to Lipinski's 5th law as a physicochemical basis and provides predictions of hepatotoxicity